2017
DOI: 10.1038/srep40927
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Synthesis of TiO2@Fe2O3 Core-Shell Nanotube Arrays with Double-Wall Coating as Superb Lithium-Ion Battery Anodes

Abstract: Highlighted by the safe operation and stable performances, titanium oxides (TiO2) are deemed as promising candidates for next generation lithium-ion batteries (LIBs). However, the pervasively low capacity is casting shadow on desirable electrochemical behaviors and obscuring their practical applications. In this work, we reported a unique template-assisted and two-step atomic layer deposition (ALD) method to achieve TiO2@Fe2O3 core-shell nanotube arrays with hollow interior and double-wall coating. The as-prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 40 publications
2
33
0
Order By: Relevance
“…2426 However, although several reports can be found on utilization of the ALD coatings of different materials to modify the electrodes for lithium-ion battery application, 2733 only one publication reports on the use of ALD to coat an anode prepared from an anodic TiO 2 nanotube layer with ZnO. 23 …”
Section: Introductionmentioning
confidence: 99%
“…2426 However, although several reports can be found on utilization of the ALD coatings of different materials to modify the electrodes for lithium-ion battery application, 2733 only one publication reports on the use of ALD to coat an anode prepared from an anodic TiO 2 nanotube layer with ZnO. 23 …”
Section: Introductionmentioning
confidence: 99%
“…Recent progress has been recorded in exploring new heterological hybrid designs, for instance, core-shell, and yolk-shell among TiO 2 -B nanowires and metal oxides (SnO 2 , anatase TiO 2 , Fe 2 O 3 ) (Figure 5). 60,[120][121][122][123][124][125] The effective combination of the two active materials in one smart morphological electrode system has promised to provide excellent cycle and rate performances at the same time. In this regard, both Zhang and Yang reported that when SnO 2 NPs or SnO 2 nanocrystals were uniformly coated on the entire surface of TiO 2 -B nanowire backbones, they formed novel core-shell designs as advanced anode materials in LIBs.…”
Section: Hierarchical Heterostructures Based On Tio 2 -B and Tmos Tmdsmentioning
confidence: 99%
“…This also created a large exposure area between the anode materials and electrolyte, facilitating the insertion/extraction of Li +. 110,122,128 More importantly, these hybrid nanostructures could largely alleviate the agglomerations for the SnO 2 NPs and also for the TiO 2 -B nanostructures. As a result, the reversible capacity reached about 1160 mAh g À1 at C/5 rate and an excellent capacity cyclability achieved 790 mAh g À1 after 30 cycles.…”
Section: Hierarchical Heterostructures Based On Tio 2 -B and Tmos Tmdsmentioning
confidence: 99%
“…This was 80% of the initial capacity comparing with 30% retention in the case of bare Si NWs under the same cycling conditions. Chao et al coated a mesoporous thin layer of PEDOT on the V2O5 nanobelt arrays (Figure 10d,10e) directly grown on the 3D ultrathin graphite foam (UGF) [145]. The thin layer can not only facilitate the electron transfer around V2O5 but also decrease the polarization and improve the reaction kinetics.…”
Section: Function-assistancementioning
confidence: 99%